Cross-reactivity between antigens of Anisakis simplex s.l. and other ascarid nematodes - Lozano Maldonado J.; Martín Hita L.; Díaz Sáez V.; Mañas Almendros I.; Valero López A.; Campos Bueno M. (Parasite, 2004)
A study of the cross-reactivity among somatic and excretory-secretory antigens of the third stage larvae of Anisakis simplex s.l. and somatic antigens of other ascarid nematodes (Ascaris lumbricoides, A. suum, Toxocara canis, Anisakis physeteris, Hysterothylacium aduncum and H. fabri) was carried out by immunoblotting. It was revealed a high degree of cross-reactivity among ascarids in the 30 and > 212 kDa range by using sera against somatic and excretory-secretory antigens of A. simplex s.l. It has been revealed also specific components of the Anisakis genus (< 7.2, 9, 19 and 25 kDa) that will be interesting in diagnosis.